Prevalence and risk factors of secondary traumatic stress in emergency call-takers and dispatchers - a cross-sectional study = Prevalencia y factores de riesgo de estrés traumático secundario en operadores de llamadas de emergencia y despachadores - un estudio transversal - Kindermann, David; Nagy, Ede; Greinacher, Anja; Cranz, Anna; Friederich, Hans-Christoph; Nikendei, Christoph (European journal of psychotraumatology, 2020)
Background: Emergency call-takers and dispatchers (ECDs) field emergency calls and dispatch the appropriate emergency services. Exposure to the callers’ traumatic experiences can lead to psychological stress and even to secondary traumatic stress (STS). In addition, previous studies suggest that ECDs may also suffer from posttraumatic stress disorder (PTSD), depression and anxiety disorders. Objectives: To investigate the prevalence of STS and to screen for PTSD, depression and anxiety disorders in ECDs. We further aimed to identify sociodemographic variables and attachment styles as possible risk factors for higher STS symptom load in ECDs. Methods: STS and PTSD regarding lifetime traumatic events, as well as depression and anxiety disorders, were investigated in N = 71 ECDs. Multiple regression analysis was performed to identify possible risk factors for higher STS symptom load. Results: The analysis determined a prevalence of 8.5% for moderate STS and 2.8% for severe STS. A total of 11.3% of the ECDs screened positive for PTSD, 15.5% for depression and 7.0% for anxiety disorders. A higher number of children and the absence of a secure attachment style were identified to be significantly associated with higher STS symptom load. Conclusions: STS resulting from exposure to traumatic emergency caller content is a common phenomenon among ECDs. Specific sociodemographic variables and the attachment style are significant risk factors of STS symptom load. ECDs should receive regular psychoeducational interventions and supervision to identify and mitigate mental distress at an early stage.
Gesehen am 20.11.2020